Limitations of small-scale yielding for fatigue crack growth. (July 2021) - Marques, B.; Borges, M.F.; Antunes, F.V.; Vasco-Olmo, J.M.; Díaz, F.A.; James, M.N.
Highlights: The validity of stress intensity factor, K, usually is not checked. A procedure to check K validity is proposed based on elastic and total CTOD. Small-scale yielding is proposed to occur when CTODe/CTODtot is>75%. LSY is promoted for higher crack lengths, minor yield stresses and in plane stress. Even for high strength alloys like Ti6Al4V, the validity of SSY should be checked. Abstract: The work described here has led to a simple criterion that defines the boundary of the small-scale yielding, SSY, regime to avoid invalid use of the LEFM parameter, ΔK, as the characterising parameter for fatigue crack growth rate. The approach proposed is based on the analysis of crack tip opening displacement, CTOD, and its separation into elastic and plastic components. SSY conditions are shown to dominate when the elastic component of CTOD is >75% of the total CTOD measured at a distance of 8 μm (the finite element mesh size) behind the crack tip, i.e., Δδe / Δδt > 75%. Large-scale yielding, LSY, conditions become dominant for relatively large values of plastic CTOD, Δδe / Δδt < 60%. An increase in crack length (and therefore of ΔK ), a decrease in yield stress of the material and the existence of plane stress conditions all promote LSY. The results obtained from various loading and geometric conditions simulated in this work demonstrate that caution should be used in assuming that the use of ΔK is valid even for high strength alloys like Ti6Al4V. In this material, the boundary of the elastic regime was crossed and SSY conditions lost, for the longest crack lengths studied and in the case of overloads.